تحري درجة تعبير الكولاجين IV في الغشاء القاعدي حول جزر خلايا السرطان البشروي شائك الخلايا الفموي - بركات شريف (Latakia University Journal -Medical Sciences Series, 2019)
مقدمة: تعتمد سرعة انتشار السرطان البشروي شائك الخلايا على مدى سرعة تخرب degradation أو عدم استمرارية Discontinuity الغشاء القاعدي، يعتبر تخرب الغشاء القاعدي المرحلة الأولى من غزو الخلايا السرطانية cancer cell invasion واجتياحها metastasis مما له أثر بالغ على حياة المريض وإنذار الحالة . الهدف من البحث: دراسة درجة التعبير عن الكولاجين IV في الغشاء القاعدي حول الجزر الورمية في سياق الإصابة بالسرطان البشروي شائك الخلايا في الحفرة الفموية . المواد والطرق: 25 حالة سرطان شائك الخلايا مأخوذة من مناطق مختلفة من الحفرة الفموية درست نسيجياً وتمّ تلوينها مناعياً بكاشف الكولاجين IV . النتائج: لحسن الحظ أظهرت دراستنا أنّ معظم السرطانات البشروية شائكة الخلايا كانت جيدة التمايز، فيما يخص دراسة الغشاء القاعدي حول الجزر الورمية وهي النقطة الجوهرية التي ركزنا عليها في بحثنا؛ فلدى دراسة درجة التعبير عن الكولاجين IV في الغشاء القاعدي المحيط بالجزر الورمية لحالات السرطان البشروي شائك الخلايا تبين لنا أنّ الغشاء القاعدي كان إيجابياً بنسبة مئوية قدرها 76% مما يوحي بإنذار أفضل . ولدى دراسة النسبة المئوية لدرجة إيجابية الغشاء القاعدي حول الجزر الورمية نجد أنّ نسبة قدرها 40% من الحالات كانت فيها الإيجابية للكولاجين IV بين 40-60% ، وبمعنى آخر إنّ الغشاء القاعدي أصبح متقطعاً (أو على الأقل تغير تركيب الكولاجين IV حول الجزر الورمية ) . المناقشة: كلّما زادت درجة التعبير عن الكولاجين IV في الغشاء القاعدي كانت القدرة على الغزو والاستعمار أضعف الأمر الذي يرفع معدل البقاء على قيد الحياة . وبالتالي من الممكن التنبؤ بإنذار الحالة من خلال تحري درجة التعبير عن الكولاجينIV حول الجزر الورمية في السرطان البشروي شائك الخلايا في الحفرة الفموية . BACKGROUND: The speed of the spread of squamous cell carcinoma (SCC) depends on the speed of the degradation or discontinuity of the basement membrane. The degradation of the basement membrane is considered the stage of the cancer cell invasion and metastasis, which has a large impact on the prognosis. This study aims to study the expression of collagen IV in the basement membrane around the nests of tumor cells in oral squamous cell carcinoma. METHODS: 25 cases of oral squamous cell carcinoma are taken from different areas of the oral cavity, we approach histological and ummunohistochemical study with antibody of the collagen IV. RESULTS: fortunately, the research showed that most of the SCC were well-differentiated. As for the study of the basement membrane around the nests of tumor cells, which is the essence of the research: when we study collagen IV degree of expression in the basement membrane surrounding the nests of tumor cells in SCC, we found out that the basement membrane was 76% positive, which reveals a better prognosis. When studying the percentage of the positivity of the basement membrane around the nests of tumor cells, we found out that in 40% of the case, the positivity of the collagen IV was between 40- 60%. In other words, the basement membrane became discontinuous (or at least the structure of the collagen IV in the nests of tumor cell has changed). The more the degree of expression of collagen IV in the basement membrane, the less capability of invasion or metastasis is, which increases the rates of survival. CONCLUSIONS: It is possible to predict the prognosis via exploring the degree of the expression of the collagen IV around the nests of tumor cells in SCC in the oral cavity.